Avaliação do perfil de citocinas na secreção endocervical de pacientes com nic II e III tratadas com interferon alfa peguilado - MUNDIM, Fabiano Vilela (2017)
Cervical intraepithelial neoplasia as a consequence of the carcinogenic transformation caused by HPV is now one of the main intercurrent factors in the female genital tract. In addition to invasive cervical cancer; interventions such as conization and LEEP can lead to obstetric complications, with consequent infertility. Advances in understanding the immune system have led to new treatment strategies. Cytokines are a group of molecules involved in the emission of signals between cells during immune responses, and among them, interferon plays an essential role in antiviral protection mechanisms, exerting potent immunomodulatory effects and in controlling cell growth. Stimulating the immune system to recognize modified or infected cells has been a major challenge. In this way, the local immune response in the secretions of patients with high grade neoplastic lesions treated with pegylated IFN-α 2b was evaluated. A six-dose therapy (Interferon α 2b pegylated) was performed in 16 patients diagnosed with high-grade lesions; (IL-2, IL-12, TNF, IFN-γ, TGF-β, IL-4, IL-10) were collected during the specular inspection by enzyme-linked immunosorbent assay (ELISA). As a study methodology, the patients were divided into three groups (General, Good and Bad responses) based on the results of the biopsies collected during the treatment; before therapy (1st application) and after treatment (6th application). The Friedman and Mann-Whitney statistical tests were used for the evaluation of the results, considering the significant sampling when p≤0.05. In view of the results obtained, it was verified that 43.75% of the patients had a satisfactory clinical response. In the evaluation of cytokines, large variations were observed during therapy, with significant changes throughout the treatment and between the application periods, of which we can highlight the TGF-β (General group), with a significant decrease during the treatment with all patients (P = 0.035), and between the 1st and 4th and 4th and 5th applications (p = 0.0420 / p = 0.0285). The cytokine TNF-α in the group of patients with good response to therapy had the same statistically significant reduction profile (p = 0.011 / p = 0.070 / p = 0.0379) during the application periods (1st and 6th, 2nd and 6th and 4th and 6th applications), tending to maintain this aspect at the end of therapy. In the analysis of IL-4 among the group of patients with poor response, significant results (p = 0.018 / p = 0.0258) were observed with a decrease during the applications (1st and 5th and 1st and 6th applications). In addition, it was also observed that this cytokine presented significant data in the 1st application when comparing the two groups of patients (Good and Bad responses) during the periods of therapy (p = 0.0229). These data allow us to conclude that the predominant profile in those patients who failed therapy appears to be associated with increased levels of IL-4 at the start of treatment; and that even a decrease in TGF-β and TNF-α may be related to those patients who responded to treatment. However, immunotherapy with pegylated IFNα-2b has been shown to be satisfactory when compared to other similar studies in the literature, suggesting that this treatment may be a therapeutic option in the future, especially for young women, where aggressive treatment of neoplasias and its complications can be avoided.